Experiments in norms, cooperation and culture - Surachita, Shruti (2022)
Norms are informal rules shaped and transmitted by social learning that determine aggregate behavioural patterns in society. This could range from simple rules such as those associated with social etiquette to the currently relevant ones related to the Covid-19 pandemic. This thesis contributes to the literature exploring social norms, particularly the role of such consideration in social dilemma problems, issues with its measurement and investigating the underlying mechanisms driving these patterns. The thesis includes three independent research studies that use a combination of online and laboratory experiments investigating these issues. Chapter 1 briefly introduces the research objectives, discusses the methods used and summarises the overall contributions from all the 3 studies. Chapter 2 investigates the influence of varying degrees of saliency of a cooperative norm on contribution choices as well as the effect of (induced) cooperation as a function of initial saliency on the perceptions of a norm of cooperation. We find that saliency improves cooperation only in round 1 in a repeated public goods game, and cooperation still decays with time. Additionally, norm of cooperation remains stable, irrespective of the local experience in the game. Chapter 3 tests the effectiveness of two preference elicitation methods in a simple rule-following experiment. There is evidence of preference conditionality with people’s rule following behavioural decisions, but limited experimental methods exist to measure such preferences. We find that a variant of the strategy method (Gächter et al., 2021) captures such preferences accurately and is also useful in eliciting preference heterogeneity in individuals with regards to their adherence towards rule compliance. Chapter 4 studies the social beliefs and peoples’ conformity attitudes in two countries namely Sweden and Turkey that vary in their degree of individualism. We find that the individualistic cultural orientation with efficient formal institution in Sweden helps shape clear normative message of rule-compliance, which is not the case in Turkey. Chapter 5 concludes with a brief overview of the contribution and scope for future research.